Frantz Fanon and Decolonization - Silveira, Renato da (2022)
In 1952, an unknown Martinican physician named Frantz Fanon published a blunt critique of structural racism in the region of the former French Empire. His book, Black Skin, White Masks, besides being a pioneering outline, in psychiatric terms, of the alienation caused by racism, introduced a number of innovations such as interdisciplinarity and processualism that would later be adopted by the social sciences. But he also revealed a disappointment with the treatment he received in the metropolis and a dissatisfaction with the contestation movements of the time, concluding his work with more dilemmas than solutions. In the following years Fanon would become a world-respected anti-colonialist militant, as leader of the National Liberation Front of Algeria. Months before his death, he published The Wretched of the Earth, a harsh critique of political solutions in post-colonial Africa. However, at a time when the social movement was diversifying internationally and post-coloniality was lending more prominence to traditional cultures, he systematically disregarded those cultures, overestimating the role of revolutionary parties, which, victorious, ended up disappointing militant humanity by instituting a kind of neo-absolutism and creating new systems of exploitation and oppression.